2002
DOI: 10.1111/j.1365-2621.2002.tb09550.x
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of Fermented Lactic Beverages Containing Probiotic Cultures

Abstract: Lactic beverages (LB) are products prepared with yogurt, whey, and other ingredients; they are popular among consumers in Brazil. LB containing probiotics were manufactured to study bacteria viability and to evaluate product characteristics during shelf life. Although counts decreased, 5.3 x 10 6 CFU/mL of probiotics in average after 28 d were found. LB behaved as pseudoplastic fluids with thixotropy, and flow curves were best fitted by Oswald-de-Waele model. Apparent viscosity and pH decreased slightly with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
41
2
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 16 publications
10
41
2
8
Order By: Relevance
“…Oliveira et al (13) reported similar results for counts of Str. thermophilus in fermented lactic beverages containing probiotic bacteria.…”
Section: Viable Cell Counts Of the Fermented Milkssupporting
confidence: 63%
“…Oliveira et al (13) reported similar results for counts of Str. thermophilus in fermented lactic beverages containing probiotic bacteria.…”
Section: Viable Cell Counts Of the Fermented Milkssupporting
confidence: 63%
“…4). This thixotropic effect occurs as a result of structural breakdown and can be estimated by considering the area of the hysteresis loop between the two curves [26]. Similar results have been reported for dairy fermented beverages [27][28][29] and for fermented beverages made from WSSE [6].…”
Section: Rheological Behaviorsupporting
confidence: 67%
“…The Casson model did not exhibit negative values for yield stress, but the determination coefficients in this model were lower than those found using the Ostwald-de-Waelle model. Therefore, as has been observed in many studies of fermented dairy beverages and fermented soymilk beverages, the model of Ostwald-de-Waelle (Power law) best fit the experimental data [9,26,34]. The power law model explained between 84.52% and 93.27% of the variation in the experimental data, meaning that this model can be used to explain the rheological behavior of the yogurt-like beverages analyzed.…”
Section: Rheological Modelingmentioning
confidence: 78%
See 1 more Smart Citation
“…Fermented foods are of great importance world-wide because their nutritional, organoleptic and shelf-life properties are significantly improved when compared with their raw materials (Oliveira et al, 2002). Yogurt is defined as fermented milk produced by fermentation with two species of lactic acid bacteria, Streptococcus thermophilus and Lactobacillus bulgaricus, which are active in a symbiotic relationship.…”
Section: Introductionmentioning
confidence: 99%